Composite laminate structure for solid-state battery and preparation method thereof

CN119009198BActive Publication Date: 2025-01-28INX ENERGY TECHNOLOGY (JIANGSU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411500358.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The stability of the solid electrolyte contact with the negative electrode in solid-state batteries is poor, resulting in uneven current distribution, abnormal lithium deposition, forming lithium crystal branches, thereby reducing the safety performance of the battery.

Method used

The composite layer is used, including the ceramic layer and conductive layer of the layers of stacked, and form a integrated structure through a coexistence process. The film in the ceramic layer and the conductive layer is formed before co -burning. Phase materials, the quality ratio of phase materials and negative metal materials is (0 ~ 5): (95 ~ 100), and the melting point of the phase material is 300 ~ 1000 ° C.

Benefits of technology

A close combination of solid electrolyte and negative electrode, reducing the interface pore rate, avoiding the growth of lithium abnormal deposition and lithium crystal branches, and improving the safety performance of solid battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119009198B_ABST
    Figure CN119009198B_ABST
Patent Text Reader

Abstract

The embodiment of the present application discloses a composite laminate structure for solid-state batteries and a preparation method thereof. The composite laminate structure includes a ceramic layer and a conductive layer arranged in layers, wherein the ceramic layer and the conductive layer are formed into an integral structure by a co-firing process, and at least one of the thin film corresponding to the ceramic layer and the thin film corresponding to the conductive layer is formed by a tape casting technology before the co-firing process; the conductive layer includes a negative electrode metal material and a phase material, wherein the mass ratio of the phase material to the negative electrode metal material is (0~5):(95~100), and the melting point of the phase material is 300~1000℃, thereby achieving a close combination between the solid electrolyte and the negative electrode of the solid-state battery, solving the problem of poor stability of the contact between the solid electrolyte and the negative electrode, and effectively avoiding the abnormal deposition of lithium between the solid electrolyte and the negative electrode and the growth of lithium dendrites.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid-state batteries, and in particular to a composite laminate structure for solid-state batteries and a preparation method thereof. Background Art

[0002] Solid-state batteries are a new type of battery technology that uses solid electrolytes to replace the liquid electrolytes and separators in traditional lithium-ion batteries. Solid-state batteries have higher safety, longer service life and higher energy density. Solid-state batteries do not contain flammable organic components, so they have significant advantages in safety and stability compared to traditional liquid lithium-ion batteries.

[0003] In the related technology, the contact stability between the solid electrolyte and the negative electrode is poor, which easily leads to uneven current distribution, resulting in abnormal lithium deposition during the battery charging and discharging process, leading to the formation of lithium dendrites, and then causing the battery to short circuit, greatly reducing the safety performance of the solid-state battery. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present application provides a composite laminate structure for a solid-state battery and a preparation method thereof, aiming to solve the technical problem of poor stability of the contact between the solid electrolyte and the negative electrode in the prior art.

[0005] To solve the above problems, in a first aspect, the present application provides a composite laminate structure for a solid-state battery, which comprises a ceramic layer and a conductive layer stacked in layers, wherein the ceramic layer and the conductive layer are formed into an integral structure through a co-firing process;

[0006] Wherein, at least one of the thin film corresponding to the ceramic layer and the thin film corresponding to the conductive layer is formed by tape casting technology before the co-firing process;

[0007] The conductive layer includes a negative electrode metal material and a phase material, the mass ratio of the phase material to the negative electrode metal material is (0-5): (95-100), and the melting point of the phase material is 300-1000°C.

[0008] Further, in the composite laminate structure for solid-state batteries provided in the present application, the ceramic layer includes a garnet-type ceramic electrolyte, and the molecular formula of the garnet-type ceramic electrolyte includes: Li x LqCy y Ta z O 12 , where 6<x≤7, 1<y≤2, 0≤z≤1.

[0009] Furthermore, in the composite laminate structure for a solid-state battery provided in the present application, the negative electrode metal material includes nickel metal, the phase material includes a glass phase material, and the melting point of the glass phase material is 600-800°C.

[0010] Furthermore, in the composite laminate structure for solid-state batteries provided in the present application, the glass phase material includes at least one of silicon oxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide and titanium oxide.

[0011] Furthermore, in the composite laminate structure for solid-state batteries provided in the present application, the mass ratio of the glass phase material to the nickel metal is (2~4): (96~98).

[0012] In a second aspect, the present application also provides a method for preparing a composite laminate structure for a solid-state battery, which comprises the following steps:

[0013] S1. Provide ceramic electrolyte materials and negative electrode metal materials;

[0014] S2, preparing the ceramic electrolyte material and the negative electrode metal material into a first slurry and a second slurry respectively, and performing tape casting on the first slurry and the second slurry to obtain a solid electrolyte membrane and a conductive membrane; wherein the second slurry comprises a negative electrode metal material and a phase material, the mass ratio of the phase material to the negative electrode metal material is (0-5): (95-100), and the melting point of the phase material is 300-1000°C;

[0015] S3, hot pressing the solid electrolyte membrane and the conductive membrane to obtain a composite film;

[0016] S4. Sintering the composite film to obtain a composite laminate structure for a solid-state battery.

[0017] Further, in the preparation method of the composite laminate structure for solid-state batteries provided in the present application, the first slurry comprises a garnet-type ceramic electrolyte, an organic solvent, a dispersant, a binder and a plasticizer; or / and,

[0018] The second slurry comprises nickel metal, glass phase material, organic solvent, dispersant, binder and plasticizer; or / and,

[0019] The particle size of the ceramic electrolyte is 0.05-1 μm; or / and,

[0020] The particle size of the nickel metal is 0.5-5 μm.

[0021] Furthermore, in the preparation method of the composite laminate structure for solid-state batteries provided in the present application, the first slurry comprises: 35-50 weight components of garnet-type ceramic electrolyte, 50-65 weight components of organic solvent, 0-1 weight component of dispersant, 1-10 weight components of binder and 0-10 weight component of plasticizer; or / and,

[0022] The second slurry includes 34-49 weight components of nickel metal, 0-2 weight components of glass phase material, 50-65 weight components of organic solvent, 0-1 weight component of dispersant, 1-10 weight components of binder and 0-10 weight component of plasticizer.

[0023] Furthermore, in the preparation method of the composite laminate structure for solid-state batteries provided in the present application, the dispersant includes at least one of fish oil, triethanolamine, and triolein.

[0024] Further, in the method for preparing a composite laminate structure for a solid-state battery provided in the present application, the pressure of the hot pressing is 3-12 MPa, the temperature of the hot pressing is 50-80° C., and the time of the hot pressing is 1-5 min; or / and,

[0025] The sintering temperature is 1000-1500° C., the sintering time is 5-15 min, and the sintering heating rate is 5-50° C. / min.

[0026] In a third aspect, the present application further provides a solid-state battery, which comprises the composite laminate structure provided in the first aspect or the composite laminate structure prepared by the preparation method provided in the second aspect.

[0027] The composite laminate structure for a solid-state battery provided in the present application includes a ceramic layer and a conductive layer stacked in layers, wherein the ceramic layer and the conductive layer are formed into an integral structure through a co-firing process, and at least one of the thin films corresponding to the ceramic layer and the thin films corresponding to the conductive layer is formed by a tape casting technology before the co-firing process; the conductive layer includes a negative electrode metal material and a phase material, wherein the mass ratio of the phase material to the negative electrode metal material is (0~5):(95~100), and the melting point of the phase material is 300~1000°C, thereby achieving a close combination between the solid electrolyte and the negative electrode of the solid-state battery, solving the problem of poor stability of the contact between the solid electrolyte and the negative electrode of the solid-state battery, and being able to effectively avoid the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0029] Figure 1 A schematic diagram of a composite laminate structure for a solid-state battery provided in an embodiment of the present application;

[0030] Figure 2 A first topographical image of a composite laminate structure for a solid-state battery provided in an embodiment of the present application;

[0031] Figure 3 A second morphological image of the composite laminate structure for a solid-state battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0033] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or combinations thereof.

[0034] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the application. As used in this application specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.

[0035] It should be further understood that the term “and / or” used in the specification and appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0036] As mentioned in the background technology of this application, the interface chemical stability between the solid electrolyte and the negative electrode of existing solid-state batteries is poor, and lithium dendrites are easily grown on the metal surface. In order to solve the technical problem of poor interface chemical stability between the solid electrolyte and the metal negative electrode, this application provides a composite laminate structure and its preparation method, and a solid-state battery.

[0037] See also Figure 1 , Figure 1 Schematic diagram of a composite laminate structure for a solid-state battery provided in an embodiment of the present application. Figure 1 As shown, in one embodiment of the present application, a composite laminate structure for a solid-state battery includes a ceramic layer 100 and a conductive layer 200 stacked in layers, wherein the ceramic layer 100 and the conductive layer 200 are formed into an integral structure through a co-firing process;

[0038] Wherein, at least one of the thin film corresponding to the ceramic layer 100 and the thin film corresponding to the conductive layer 200 is formed by tape casting technology before the co-firing process;

[0039] The conductive layer 200 includes a negative electrode metal material and a phase material, the mass ratio of the phase material to the negative electrode metal material is (0-5): (95-100), and the melting point of the phase material is 300-1000°C.

[0040] Specifically, the ceramic layer 100 and the conductive layer 200 can be integrally formed by hot pressing and sintering, thereby achieving a close bond between the solid electrolyte and the negative electrode metal, so that there will be no obvious cross-sectional pores between the ceramic layer 100 and the conductive layer 200, effectively avoiding the growth of lithium dendrites caused by abnormal lithium deposition between the solid electrolyte and the negative electrode.

[0041] Casting technology is a molding process used to prepare films or sheets. Its basic principle is to form a film of a certain thickness on a substrate through a scraper or a die, and then make the final product through steps such as drying and sintering.

[0042] The present application adopts the tape casting technology to generate the solid electrolyte membrane corresponding to the ceramic layer and the conductive membrane corresponding to the conductive layer. It not only takes into account the uniform distribution of the solid electrolyte in the solid electrolyte membrane and the uniform distribution of the metal material in the conductive membrane, but also takes into account the thickness and deformation of the solid electrolyte membrane and the conductive membrane. If the solid electrolyte membrane and the conductive membrane do not adopt the tape casting technology, the thickness of the solid electrolyte membrane and the conductive membrane finally generated is large and easy to deform, resulting in the need for processing of the solid electrolyte membrane and the conductive membrane, which not only increases the production cost, but also makes the processing more difficult. At the same time, after the solid electrolyte membrane and the conductive membrane are assembled and bonded, it is easy to have an interface gap, which affects the conductive performance.

[0043] Furthermore, the present application also adds a phase material to the conductive layer 200, the melting point of the phase material can be set to 300~1000℃, and the mass ratio of the phase material to the negative electrode metal material is (0~5):(95~100), which can reduce the surface tension of the conductive layer 200 and improve the wettability of the conductive layer 200, thereby ensuring that the conductive layer 200 and the ceramic layer 100 can be more tightly hot-pressed, and further reduce the interface porosity between the solid electrolyte and the negative electrode, so that there will be no obvious cross-sectional pores between the solid electrolyte and the negative electrode, effectively avoiding the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode.

[0044] In some embodiments, the interfacial porosity between the ceramic layer 100 and the conductive layer 200 may be between 0% and 5%.

[0045] In this embodiment, the interface porosity is also called the void ratio, porosity or cross-sectional gas content, which can be understood as the ratio of the area occupied by the cross-sectional pores at the bonding interface formed between the ceramic layer 100 and the conductive layer 200 to the area of ​​the bonding interface after the ceramic layer 100 and the conductive layer 200 are bonded and integrated. Preferably, the interface porosity can be between 0 and 1%.

[0046] Specifically, the interface porosity may be 1%, 0.5%, 0.2%, 0.1%, 0.05%, 0.025%, 0.015%, 0.005%, etc. The interface porosity between the ceramic layer 100 and the conductive layer 200 may be measured by direct measurement, image analysis, microscopy, density method, etc.

[0047] In some embodiments, the ceramic layer 100 includes a ceramic electrolyte. Specifically, the ceramic electrolyte is a type of solid material with high ionic conductivity and excellent mechanical strength, which is widely used in solid-state batteries. The main advantage of the ceramic electrolyte is that it can effectively solve the safety problems such as combustion and explosion that may be caused by traditional liquid electrolytes during use.

[0048] In this embodiment, the ceramic electrolyte may be a garnet-type LLZTO (lithium lanthanum zirconium oxide, Li7La3Zr2O 12 ), perovskite type (lithium lanthanum titanate / lithium lanthanum titanate, Li 0.33 La 0.56 TiO3), NASICON (sodium superionic conductors, such as lithium aluminum titanium phosphate, Li 1.3 Al 0.3 Ti 1.7 (PO4)3) type, LISICON (lithium superion conductor, such as Li 4-x Zn 2xGeO4, 0≤x≤1) type and layered LiN3, etc. Preferably, the ceramic electrolyte may be a garnet type ceramic electrolyte.

[0049] In some embodiments, the molecular formula of the garnet-type ceramic electrolyte includes: Li x LqCy y Ta z O 12 , wherein 6<x≤7, 1<y≤2, 0≤z≤1. Preferably, the molecular formula of the garnet-type ceramic electrolyte may be Li 6.4 LqCy 1.4 Ta 0.6 O 12 .

[0050] Among them, garnet ceramic electrolytes have high room temperature ionic conductivity (10 -3 S cm -1 ) and its stability to lithium metal and is widely used. However, garnet-type ceramic electrolytes easily react with water and carbon dioxide in the air, resulting in poor stability. In the present application, after hot-pressing the garnet-type ceramic electrolyte and the negative electrode material in the form of a thin film, it can be ensured that the garnet-type ceramic electrolyte and the negative electrode material are tightly combined, which greatly reduces the interface porosity between the solid electrolyte and the negative electrode, reduces the probability of the garnet-type ceramic electrolyte easily reacting with water and carbon dioxide in the air, and greatly improves the stability of the contact between the solid electrolyte and the negative electrode.

[0051] In addition, the garnet-type ceramic electrolyte provided in the present application can also be compounded with other polymers or ceramic materials to further improve the mechanical strength and ionic conductivity of the ceramic layer 100. For example, the nanoparticles of the garnet-type ceramic electrolyte are uniformly dispersed in the PEO / LiTFSI polymer electrolyte, which can significantly improve the ionic conductivity and mechanical properties of the ceramic layer 100.

[0052] In some embodiments, the conductive layer 200 includes nickel metal, graphite or metallic lithium. Preferably, the conductive layer 200 contains nickel metal, which can improve the energy density and power capacity of the solid-state battery, and can also effectively reduce the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode.

[0053] Further, in some embodiments, the phase material includes at least one of silicon oxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide, and titanium oxide.

[0054] In this embodiment, the phase material may be a glass phase material with a low melting point. Preferably, the melting point of the glass phase material is preferably 600-800°C. The glass phase material may be composed of three or more of silicon oxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide and titanium oxide, which can ensure that the conductive layer 200 and the ceramic layer 100 can be more closely hot-pressed, and further reduce the interface porosity between the solid electrolyte and the negative electrode, so that there is no obvious cross-sectional pore between the solid electrolyte and the negative electrode, effectively avoiding the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode.

[0055] Among them, silicon oxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide and titanium oxide can be silicon dioxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide and titanium dioxide respectively.

[0056] In some embodiments, the negative electrode metal material may be nickel metal, and the phase material may be mixed with the nickel metal in the form of doping, that is, the mass ratio between the phase material and the nickel metal may be (0-5): (95-100). Preferably, the mass ratio between the phase material and the nickel metal material may be (1-5): (95-99), or (1-4): (96-99), or (2-4): (96-98), etc.

[0057] Specifically, the phase material may be a glass phase material, and the mass ratio between the glass phase material and the nickel metal material may be 3:97, which may further improve the wettability of the conductive layer 200 , thereby ensuring that the conductive layer 200 and the ceramic layer 100 can be more closely hot-pressed together.

[0058] The composite laminate structure for a solid-state battery provided in the present application includes a ceramic layer 100 and a conductive layer 200 which are stacked. The ceramic layer 100 and the conductive layer 200 are formed into an integral structure through a co-firing process, thereby achieving a close bond between the solid electrolyte and the negative electrode of the solid-state battery, solving the problem of poor stability of the contact between the solid electrolyte and the negative electrode of the solid-state battery, and being able to effectively avoid the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode of the solid-state battery.

[0059] In some embodiments, the present application also provides a method for preparing a composite laminate structure for a solid-state battery, which comprises the following steps:

[0060] S1. Provide ceramic electrolyte materials and negative electrode metal materials;

[0061] S2, preparing a ceramic electrolyte material and a negative electrode metal material into a first slurry and a second slurry respectively, and performing tape casting on the first slurry and the second slurry to obtain a solid electrolyte membrane and a conductive membrane; wherein the second slurry comprises a negative electrode metal material and a phase material, the mass ratio of the phase material to the negative electrode metal material is (0-5): (95-100), and the melting point of the phase material is 300-1000°C;

[0062] S3, hot pressing the solid electrolyte membrane and the conductive membrane to obtain a composite film;

[0063] S4. Sintering the composite film to obtain a composite laminate structure for a solid-state battery.

[0064] In this embodiment, the ceramic electrolyte material and the negative electrode metal material can be made into a first slurry and a second slurry respectively, that is, the ceramic electrolyte material is configured into a first slurry and the negative electrode metal material is configured into a second slurry, and the first slurry and the second slurry can be subjected to a casting process to form a solid electrolyte membrane and a conductive membrane.

[0065] Specifically, the solid electrolyte membrane and the conductive membrane are both cast films, which can ensure that the solid electrolyte and the negative electrode metal material are evenly distributed in the film. Therefore, after the solid electrolyte membrane and the conductive membrane are hot-pressed together, the contact stability between the solid electrolyte membrane and the conductive membrane is relatively high, thereby improving the contact stability between the solid electrolyte and the negative electrode of the solid-state battery.

[0066] Among them, cast film is a non-stretched, non-directional flat extruded film produced by a melt casting quenching process. It has the characteristics of high performance, high transparency, good gloss, crystallinity and hardness. It is widely used in packaging, medical, electronics and other fields, such as wrapping film, barrier film, food-grade packaging materials and other fields. The production process of cast film mainly includes melt extrusion, cooling molding, printing and winding. The production process of cast film is different from that of blown film. The cast film can be cooled and shaped on a cooling roller, and it does not need to be stretched longitudinally or transversely. Therefore, the cast film has uniform thickness, good transparency and good heat sealing properties. In addition, cast film can be divided into two types: single-layer casting and multi-layer co-extrusion casting. Among them, the production equipment of cast film includes extruder, casting unit, cooling roller, cutting equipment, etc.

[0067] Before the first slurry and the second slurry are subjected to tape casting, the first slurry and the second slurry need to be ball milled, thereby improving the uniformity and viscosity of the first slurry and the second slurry during the tape casting process. In addition, after the first slurry and the second slurry are ball milled, a vacuum degassing treatment can be performed to remove bubbles, thereby avoiding the problem of bubbles or pinholes in the tape casting process, which leads to poor stability of the contact between the solid electrolyte membrane and the conductive membrane.

[0068] In addition, in the process of generating the corresponding cast films respectively by the cast technology using the first slurry and the second slurry mentioned in the present application, PET can be used as a substrate, that is, a solid electrolyte membrane and a conductive film can be formed on PET. After the solid electrolyte membrane and the conductive film are formed on PET, the solid electrolyte membrane and the conductive film can be peeled off from PET.

[0069] At the same time, the reason why the present application adopts the casting technology to generate the solid electrolyte membrane and the conductive membrane is not only to consider the uniform distribution of the solid electrolyte in the solid electrolyte membrane and the uniform distribution of the metal material in the conductive membrane, but also to consider the thickness and deformation of the solid electrolyte membrane and the conductive membrane. If the solid electrolyte membrane and the conductive membrane do not adopt the casting technology, the thickness of the solid electrolyte membrane and the conductive membrane finally generated is large and easy to deform, resulting in the need for processing of the solid electrolyte membrane and the conductive membrane, which not only increases the production cost, but also makes the processing more difficult. At the same time, after the solid electrolyte membrane and the conductive membrane are assembled and bonded, it is easy to have an interface gap, which affects the conductive performance.

[0070] In some embodiments, the first slurry includes a garnet-type ceramic electrolyte, an organic solvent, a dispersant, a binder, and a plasticizer, and the second slurry includes nickel metal, a glassy phase material, an organic solvent, a dispersant, a binder, and a plasticizer.

[0071] Further, in some embodiments, the first slurry includes: 35~50 weight components of garnet-type ceramic electrolyte, 50~65 weight components of organic solvent, 0~1 weight component of dispersant, 1~10 weight components of binder and 0~10 weight component of plasticizer, and the second slurry includes 34~49 weight components of nickel metal, 0~2 weight components of glass phase material, 50~65 weight components of organic solvent, 0~1 weight component of dispersant, 1~10 weight components of binder and 0~10 weight component of plasticizer.

[0072] In some embodiments, the particle size of the ceramic electrolyte is 0.05-1 μm, and the particle size of the nickel metal is 0.5-5 μm.

[0073] Specifically, the first slurry and the second slurry are respectively cast into a solid electrolyte membrane and a conductive membrane. After the solid electrolyte membrane and the conductive membrane are hot-pressed to form a composite film, since the particle size of the ceramic electrolyte in the first slurry is set between 0.05 and 1 μm, and the negative electrode metal material in the second slurry, such as nickel metal, is set between 0.5 and 5 μm, the densification between the solid electrolyte membrane and the conductive membrane can be ensured after the composite film is sintered, thereby effectively avoiding the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode of the solid-state battery.

[0074] In some embodiments, the organic solvent includes at least one of ethanol, ethyl acetate, n-butanol, acetone, and toluene, the dispersant includes at least one of fish oil, triethanolamine, and triolein, the binder includes polyvinyl butyral, and the plasticizer includes butyl phthalate. Preferably, the organic solvent includes at least two of ethanol, ethyl acetate, and n-butanol, thereby ensuring the uniformity of the garnet-type ceramic electrolyte and the nickel metal in their respective slurries.

[0075] In some embodiments, the thickness of the solid electrolyte membrane may be 0.01 to 1 mm. The thickness of the solid electrolyte membrane may be determined according to a specific process. For example, when the thickness of the solid electrolyte membrane is formed by tape casting technology, the thickness of the solid electrolyte membrane may be between 0.01 and 1 mm. Preferably, the thickness of the solid electrolyte membrane is 0.03 to 0.1 mm.

[0076] In some embodiments, the thickness of the conductive film may be 0.005-0.1 mm. The thickness of the conductive film may be determined according to a specific process. For example, when the thickness of the conductive film is formed by tape casting technology, the thickness of the conductive film may be between 0.005-0.1 mm. Preferably, the thickness of the conductive film may be 0.005-0.03 mm.

[0077] In some embodiments, the thickness of the composite laminate structure for a solid-state battery may be 10 to 1080 μm. Preferably, the thickness of the composite laminate structure for a solid-state battery may be 15 to 120 μm.

[0078] In this embodiment, after the solid electrolyte membrane and the conductive membrane are hot pressed and sintered, the thickness change that occurs is at the micron level, that is, after the solid electrolyte membrane and the conductive membrane are hot pressed and sintered, the thickness will be reduced by 5 to 20 μm. Preferably, the thickness of the solid electrolyte membrane and the conductive membrane will be reduced by 10 to 15 μm after hot pressed and sintered.

[0079] In some embodiments, the hot pressing pressure is 1-10 MPa, the hot pressing temperature is 60-100° C., the hot pressing time is 1-3 min, the sintering temperature is 1000-1500° C., and the sintering time is 5-15 min.

[0080] In this embodiment, when the solid electrolyte membrane and the conductive membrane are hot-pressed, the hot-pressing pressure can be controlled between 1 and 10 MPa, the hot-pressing temperature can be controlled between 60 and 100°C, and the hot-pressing time can be controlled between 1 and 3 minutes, which can not only ensure that the solid electrolyte membrane and the conductive membrane are tightly combined, but also ensure that the morphology of the solid electrolyte membrane and the conductive membrane will not change significantly. Preferably, the hot-pressing pressure can be 5 MPa, the hot-pressing temperature can be 80°C, and the hot-pressing time can be 2 minutes.

[0081] In addition, after the solid electrolyte membrane and the conductive membrane are hot-pressed together, the composite film after hot-pressing needs to be sintered to achieve densification between the solid electrolyte membrane and the conductive membrane, thereby completing the integral molding of the solid electrolyte membrane and the conductive membrane.

[0082] Specifically, the sintering temperature can be 1000-1500° C., and the sintering time can be 5-15 minutes, thereby ensuring that the solid electrolyte membrane and the conductive membrane can be physically bonded together to form an integral body, so that the components of the solid electrolyte membrane and the conductive membrane will not chemically react.

[0083] Preferably, the sintering temperature may be 1300° C., and the sintering time may be 10 min.

[0084] In addition, during the sintering process, the composite film needs to be sintered in an argon environment, and the sintering temperature rise rate should be as fast as possible. The sintering temperature rise rate can be controlled between 5 and 50°C / min, such as 5°C / min, 10°C / min, 15°C / min, 20°C / min, 30°C / min, 40°C / min, 50°C / min, etc., so that the densification between the solid electrolyte membrane and the conductive membrane can be ensured after the composite film is sintered, thereby effectively avoiding the growth of lithium dendrites caused by abnormal lithium deposition between the solid electrolyte and the negative electrode of the solid-state battery.

[0085] In some embodiments, the present application also provides a solid-state battery, which includes the composite laminate structure for a solid-state battery provided in the above embodiments.

[0086] The beneficial effects of the present application are further illustrated below in conjunction with the embodiments.

[0087] Example 1

[0088] S1, 40 weight components of LLZTO ceramic powder, 60 weight components of ethanol, 0.5 weight components of triethanolamine, 5 weight components of polyvinyl butyral, and 5 weight components of butyl phthalate are configured into a first slurry, and the first slurry is ball-milled and then prepared by using a casting technology to obtain a solid electrolyte membrane;

[0089] S2, preparing a second slurry with 40 weight components of high-purity nickel powder (purity> 99%), 60 weight components of ethanol, 0.5 weight components of triethanolamine, 5 weight components of polyvinyl butyral, and 5 weight components of butyl phthalate, and preparing a conductive film by ball milling the second slurry using a casting technique;

[0090] S3, cutting the solid electrolyte membrane and the conductive membrane into the same size, such as 100*100 mm, laminating the solid electrolyte membrane and the conductive membrane, hot pressing at 80° C. and a pressure of 5 MPa, maintaining the pressure for 2 min, and then releasing the pressure to obtain a composite film;

[0091] S4. Cut the composite film into required sizes, such as 50*100 mm, and place it on a ceramic support plate for degreasing and sintering. The sintering temperature is 1300°C. After a holding time of 10 minutes, a composite laminate structure for solid-state batteries is obtained.

[0092] Example 2

[0093] S1, 40 weight components of LLZTO ceramic powder, 60 weight components of ethanol, 0.5 weight components of triethanolamine, 5 weight components of polyvinyl butyral, and 5 weight components of butyl phthalate are configured into a first slurry, and the first slurry is ball-milled and then prepared by using a casting technology to obtain a solid electrolyte membrane;

[0094] S2, after uniformly mixing 38.8 weight components of high-purity nickel powder (purity> 99%) and 1.2 weight components of low-melting-point phase powder (silicon dioxide, aluminum oxide and lithium oxide), 60 weight components of ethanol, 0.5 weight components of triethanolamine, 5 weight components of polyvinyl butyral, and 5 weight components of butyl phthalate are added to prepare a second slurry, and after ball milling, the second slurry is prepared by using a casting technology to obtain a conductive film;

[0095] S3, cutting the solid electrolyte membrane and the conductive membrane into the same size, such as 100*100 mm, laminating the solid electrolyte membrane and the conductive membrane, hot pressing at 80° C. and a pressure of 5 MPa, maintaining the pressure for 2 min, and then releasing the pressure to obtain a composite film;

[0096] S4. Cut the composite film into required sizes, such as 50*100 mm, and place it on a ceramic support plate for degreasing and sintering. The sintering temperature is 1300°C. After a holding time of 10 minutes, a composite laminate structure for solid-state batteries is obtained.

[0097] Test Example 1

[0098] The bonding interfaces of the composite laminated structures for solid-state batteries prepared in the above-mentioned Examples 1 and 2 were observed by scanning electron microscopy, and the following were obtained: Figure 2 and Figure 3 The morphology shown. Among them, Figure 2 This is a topographical image of the composite laminate structure in Example 1 at 100 um, where the upper layer is a ceramic layer and the lower layer is a conductive layer; Figure 3 This is a morphology diagram of the composite laminate structure in Example 2 at 50 um, where the upper layer is a ceramic layer and the lower layer is a conductive layer.

[0099] from Figure 2 and Figure 3 It can be clearly observed that the bonding interface of the composite laminated structure prepared by Example 1 and Example 2 has no obvious cross-sectional pores, which indicates that the solid electrolyte membrane and the conductive membrane in the composite laminated structure provided by the present application are tightly bonded, which can solve the problem of poor stability of the contact between the solid electrolyte and the negative electrode, and further effectively avoid the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode.

[0100] Test Example 2

[0101] After using a micrometer to test the thickness of the solid electrolyte membrane, conductive membrane and composite laminate structure in Example 1 and Example 2, the thickness of the solid electrolyte membrane in Example 1 is 30~40μm, the thickness of the conductive membrane is 8~12μm, and the thickness of the composite laminate structure is 36~39μm; the thickness of the solid electrolyte membrane in Example 2 is 30~40μm, the thickness of the conductive membrane is 8~12μm, and the thickness of the composite laminate structure is 38~40μm.

[0102] At the same time, after the diameter of the composite laminated structure in Example 1 and Example 2 was tested with a micrometer, an Ag conductive layer was plated on the ceramic surface, and a button battery was used for packaging. Then, an electrochemical workstation MetrohmAutolab was used to perform an AC impedance test, and the test AC voltage was 10 mV and the frequency was 10 MHz~1 Hz.

[0103] After measuring the AC impedance of the composite laminated structure in Example 1 and Example 2, the ionic conductivity is calculated, and the calculation formula can be σ=L / RS, where L is the thickness of the composite laminated structure, R is the AC impedance of the composite laminated structure, and S is the single-sided area of ​​the composite laminated structure (calculated using the thickness and diameter of the composite laminated structure).

[0104] The thickness of the composite laminated structure in Example 1 is set to 36 μm and 39 μm, respectively, and the thickness of the composite laminated structure in Example 2 is set to 38 μm and 40 μm, respectively. Substituting them into the ionic conductivity calculation formula for calculation, the ionic conductivities of the composite laminated structure in Example 1 are 0.961 mS / cm and 1.042 mS / cm, respectively, and the ionic conductivities of the composite laminated structure in Example 2 are 1.207 mS / cm and 1.143 mS / cm, respectively.

[0105] It can be seen from this that the ionic conductivity of the composite film with a laminated structure provided by the present application can be close to 1 mS / cm, or even reach above 1 mS / cm, which effectively solves the problem of poor stability in the contact between the solid electrolyte membrane and the conductive membrane, and can effectively avoid the growth of lithium dendrites caused by abnormal deposition of lithium between the solid electrolyte and the negative electrode.

[0106] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A composite laminate structure for a solid-state battery, characterized in that: It comprises a ceramic layer and a conductive layer which are stacked, wherein the ceramic layer and the conductive layer are formed into an integral structure through a co-firing process; Wherein, at least one of the thin film corresponding to the ceramic layer and the thin film corresponding to the conductive layer is formed by tape casting technology before the co-firing process; the interface porosity between the ceramic layer and the conductive layer is 0-5%; The conductive layer includes a negative electrode metal material and a glass phase material, the ceramic layer includes a garnet-type ceramic electrolyte, the negative electrode metal material includes nickel metal, the particle size of the ceramic electrolyte is 0.05~1μm, and the particle size of the nickel metal is 0.5~5μm; the melting point of the glass phase material is 600~800℃; the mass ratio of the glass phase material to the nickel metal is (2~4):(96~98).

2. The composite laminate structure for solid-state batteries according to claim 1, characterized in that: The molecular formula of the garnet-type ceramic electrolyte includes: Li x Ln3Z y Ta z O 12 , where 6<x≤7, 1<y≤2, 0≤z≤1.

3. The composite laminate structure for solid-state batteries according to claim 1, characterized in that: The glass phase material includes at least one of silicon oxide, aluminum oxide, lithium oxide, zinc oxide, boron oxide and titanium oxide.

4. A method for preparing a composite laminate structure for a solid-state battery, characterized in that: The steps include: S1. Provide a ceramic electrolyte material and a negative electrode metal material; the ceramic electrolyte material comprises a garnet-type ceramic electrolyte, and the particle size of the ceramic electrolyte is 0.05-1 μm; the negative electrode metal material comprises nickel metal, and the particle size of the nickel metal is 0.5-5 μm; S2, preparing the ceramic electrolyte material and the negative electrode metal material into a first slurry and a second slurry respectively, and performing tape casting on the first slurry and the second slurry to obtain a solid electrolyte membrane and a conductive membrane; wherein the second slurry comprises a negative electrode metal material and a glass phase material, the melting point of the glass phase material is 600-800°C; the mass ratio of the glass phase material to the nickel metal is (2-4): (96-98); S3, hot pressing the solid electrolyte membrane and the conductive membrane to obtain a composite film; S4. Sintering the composite film to obtain a composite laminate structure for a solid-state battery; the interface porosity between the solid electrolyte membrane and the conductive membrane in the composite laminate structure is 0-5%.

5. The method for preparing a composite laminate structure for a solid-state battery according to claim 4, characterized in that: The first slurry further comprises an organic solvent, a dispersant, a binder and a plasticizer; or / and, The second slurry further includes an organic solvent, a dispersant, a binder and a plasticizer.

6. The method for preparing a composite laminate structure for a solid-state battery according to claim 5, characterized in that: The first slurry comprises: 35-50 weight components of garnet-type ceramic electrolyte, 50-65 weight components of organic solvent, 0-1 weight component of dispersant, 1-10 weight components of binder and 0-10 weight component of plasticizer; or / and, The second slurry includes 34-49 weight components of nickel metal, 0-2 weight components of glass phase material, 50-65 weight components of organic solvent, 0-1 weight component of dispersant, 1-10 weight components of binder and 0-10 weight component of plasticizer.

7. The method for preparing a composite laminate structure for a solid-state battery according to claim 5, characterized in that: The dispersant includes at least one of fish oil, triethanolamine and triolein.

8. The method for preparing a composite laminate structure for a solid-state battery according to claim 4, characterized in that: The hot pressing pressure is 3-12 MPa, the hot pressing temperature is 50-80° C., and the hot pressing time is 1-5 min; or / and, The sintering temperature is 1000-1500° C., the sintering time is 5-15 min, and the sintering heating rate is 5-50° C. / min.

Citation Information

Patent Citations

  • Solid state battery

    CN114127984A

  • Unit cell for fuel cell and manufacturing method thereof

    KR1020120040417A